Meanings of Abstract Art : Between Nature and Theory. - Crowther, Paul (Routledge advances in art and visual studies., 2012)
Traditional art is based on conventions of resemblance between the work and that which it is a representation "of". Abstract art, in contrast, either adopts alternative modes of visual representation or reconfigures mimetic convention. This book explores the relation of abstract art to nature (taking nature in the broadest sense-the world of recognisable objects, creatures, organisms, processes, and states of affairs). Abstract art takes many different forms, but there are shared key structural features centered on two basic relations to nature. The first abstracts from nature, to give selecte.